THE PLACE OF TERTIARY EDUCATION IN FOSTERING SELF-RELIANCE - O., Olokede N. (Sokoto Educational Review, 2020)
The quest for self-reliance has been the ubiquitous clamour and benchmark that every nation of the world strives at. Tertiary education therefore is that round peg in the round hole or rather, a catalyst for the attainment of self-reliance. This paper examines the trends in tertiary education in Nigeria. The objectives of tertiary education are also explored into. The paper also mirrors into usability of tertiary education for enhancing self-reliance. Recommendations such as overhauling of courses in tertiary institutions, establishment of more tertiary institutions to allow more intakes, adequate funding of tertiary institutions, adequate training and re-training of tertiary institutions staffers, etc. are made so as to make tertiary institutions actualize the conceived self-reliance which is the prime purpose of tertiary education..